Bluetooth windows file transfer application (BT Scout) - Auxilio, Arlyne B.; Ballesteros, Janice M.; Capati, Sherry S. (2002)
BT Scout is a Windows File Transfer application that interfaces between two Bluetooth devices. The Universal Serial Bus (USB) was used as the communications port. From the BT Scout explorer it is possible to browse among the local files of the computer and search the neighborhood for other Bluetooth devices. When connecting to a device offering the same service, a Radio Frequency Communication (RFCOMM) connection will be set up. When two devices are connected, files can be sent from any of the two devices. The standard Windows features include file view options and status information display. It also prevents overwriting of files and preserves original file date and time.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Bluetooth technology; Radio Frequency Communication (RFCOMM).; BT Scout (Computer program).